A Theoretical Outlook on the Stereoselectivity Origins of Isoselective Zirconocene Propylene Polymerization Catalysts. Issue 42 (25th June 2018) - Castro, Ludovic; Therukauff, Gabriel; Vantomme, Aurelien; Welle, Alexandre; Haspeslagh, Luc; Brusson, Jean‐Michel; Maron, Laurent; Carpentier, Jean‐François; Kirillov, Evgueni
Abstract: The first three insertion steps of propylene for isoselective metallocenes from the one‐carbon‐bridged cyclopentadienyl–fluorenyl Cp/Flu and silicon‐bridged ansa ‐bis(indenyl) SBI families were computed by using a theoretical method implementing the B3PW91 functional in combination with solvent corrections incorporated with the Solvation Model based on Density (SMD) continuum model. For C 1 ‐symmetric Cp/Flu‐type metallocenes, two mechanisms of stereocontrol were validated theoretically: more facile and more stereoselective chain "stationary" insertion (or site epimerization backskip) and less stereoselective alternating mechanisms. For the C 2 ‐symmetric SBI‐type system, the computation results were in complete agreement with the sole operating chain migratory insertion mechanism. The thermochemical data obtained through the study were used to predict microstructures of polypropylenes by using three‐parameter and one‐parameter statistical models for the two metallocene systems, respectively. The calculated meso / rac pentad distributions were found to be in good agreement with those determined experimentally for isotactic polypropylene samples obtained at different polymerization temperatures. Abstract : Origins : The origins of stereoselectivity in propylene polymerization for a series of isoselective metallocenes belonging to two different families, namely, C 1 ‐symmetric one‐carbon‐bridged cyclopentadienyl–fluorenyl type and C 2 ‐symmetric silicon‐bridged ansa ‐bis(indenyl) type systems, are elucidated by theoretical calculations by using an improved DFT model, and meso / rac pentad distributions are predicted with good precision.